Chemical characteristics and potential as functional food of seminyak leaves (Champereia manillana) - Lily Restusari; Nur Luqiana; Muharni Muharni; Dewi Rahayu (AcTion: Aceh Nutrition Journal, 2026)
Seminyak (Champereia manillana) is a local food crop from Rokan Hulu, Riau, which is often consumed as a vegetable. Although traditionally used, valid scientific information regarding its nutritional composition is limited, which hinders its development as a functional food. This study aimed to analyze the proximate nutritional and fiber content of Seminyak leaves to evaluate their potential as functional food. The proximate content (moisture, ash, protein, fat, and carbohydrates) and fiber content were analyzed using AOAC 1993 and FOSS Analytical standard methods. The results were descriptively analyzed by presenting the values obtained from these tests. The analysis results showed that Seminyak leaves have a significant protein content of 4.41% and a high ash content of 2.37%. The fat content was very low (0%). The average values of other proximate nutrients included water (78.85%), carbohydrates (9.72%), and crude fiber (2.9%). With this nutritional profile, especially the high protein and mineral (ash) content and low fat content, Seminyak leaves have great potential as a source of vegetable protein and minerals and as a raw material for developing functional food products, which can contribute to local food diversification and food security.